The Impact of Halal (Islamic) Advertisement in Youtube on Malaysian Rich Food International Brands - Hoque, Md. Obaydul; Nayeem, Abdur Rakib; Kamruzzaman, Muhammad; Ahmad, Mohd. Nazri; Abdullah, Wan Nasyrudin Wan; Akter, Mst. Fatema (International Journal of Publication and Social Studies, 2020)
The Halal idea is one of the most significant ideas regarding Muslim social orders. They decide the guidelines of their lives and day by day life exercises as per it. This circumstance additionally assumes a noteworthy part in the utilization of merchandise and enterprises and the way toward buying. Rising innovation and the changing scene have given numerous Halal items and administrations. Developing Muslim populaces have makers to deliver this sort of item improvement. Expanding buyer fulfillment levels after some time and quickly evolving inclinations, item assortment and advancement, design and comparative variables have empowered Halal items and administrations to exist in various structures on the lookout. It speaks to a brand component or strict marvel as well as is an image of life and culture. Like each image utilized in regular day to day existence, Halal, and Islamic images can transform into an item that becomes want product and can lose its significance. This paper tended to and investigated the promoting content regarding Halal publicizing and Islamic Advertising through YouTube advertisements. Other than that, the frequencies of significant inexpensive food brand's (KFC, Burger King, McDonald's, Subway) were distinguished. Methodologically, the paper used both subjective and quantitative methodologies by writing surveys the substance of the publicizing text was broke down. The discoveries demonstrated that the promoting content gave off an impression of being predictable with one another. Additionally, the Halal accentuation in publicizing varies as indicated by brands.